Prioritizing the Role of Major Lipoproteins and Subfractions as Risk Factors for Peripheral Artery Disease. Issue 5 (3rd August 2021) - Levin, Michael G.; Zuber, Verena; Walker, Venexia M.; Klarin, Derek; Lynch, Julie; Malik, Rainer; Aday, Aaron W.; Bottolo, Leonardo; Pradhan, Aruna D.; Dichgans, Martin; Chang, Kyong-Mi; Rader, Daniel J.; et al.
Abstract : Background: Lipoprotein-related traits have been consistently identified as risk factors for atherosclerotic cardiovascular disease, largely on the basis of studies of coronary artery disease (CAD). The relative contributions of specific lipoproteins to the risk of peripheral artery disease (PAD) have not been well defined. We leveraged large-scale genetic association data to investigate the effects of circulating lipoprotein-related traits on PAD risk. Methods: Genome-wide association study summary statistics for circulating lipoprotein-related traits were used in the mendelian randomization bayesian model averaging framework to prioritize the most likely causal major lipoprotein and subfraction risk factors for PAD and CAD. Mendelian randomization was used to estimate the effect of apolipoprotein B (ApoB) lowering on PAD risk using gene regions proxying lipid-lowering drug targets. Genes relevant to prioritized lipoprotein subfractions were identified with transcriptome-wide association studies. Results: ApoB was identified as the most likely causal lipoprotein-related risk factor for both PAD (marginal inclusion probability, 0.86; P =0.003) and CAD (marginal inclusion probability, 0.92; P =0.005). Genetic proxies for ApoB-lowering medications were associated with reduced risk of both PAD (odds ratio, 0.87 per 1-SD decrease in ApoB [95% CI, 0.84–0.91]; P =9×10 −10 ) and CAD (odds ratio, 0.66 [95% CI, 0.63–0.69]; P =4×10 −73 ), with a stronger predicted effect of ApoB lowering on CAD (ratio of effects, 3.09 [95% CI, 2.29–4.60]; P <1×10 −6 ). Extra-small very-low-density lipoprotein particle concentration was identified as the most likely subfraction associated with PAD risk (marginal inclusion probability, 0.91; P =2.3×10 −4 ), whereas large low-density lipoprotein particle concentration was the most likely subfraction associated with CAD risk (marginal inclusion probability, 0.95; P =0.011). Genes associated with extra-small very-low-density lipoprotein particle and large low-density lipoprotein particle concentration included canonical ApoB pathway components, although gene-specific effects were variable. Lipoprotein(a) was associated with increased risk of PAD independently of ApoB (odds ratio, 1.04 [95% CI, 1.03–1.04]; P =1.0×10 −33 ). Conclusions: ApoB was prioritized as the major lipoprotein fraction causally responsible for both PAD and CAD risk. However, ApoB-lowering drug targets and ApoB-containing lipoprotein subfractions had diverse associations with atherosclerotic cardiovascular disease, and distinct subfraction-associated genes suggest possible differences in the role of lipoproteins in the pathogenesis of PAD and CAD. Abstract : Supplemental Digital Content is available in the text.